The Virgin Mary and Catholic identities in Chinese history - Clarke, Jeremy, 1969- (Hong Kong : Hong Kong University Press, HKU, 2013)
How are Chinese Catholic identities expressed through images? In this cross-disciplinary study which engages with history, theology and art, Fr. Jeremy Clarke explores paintings and sculptures of the Virgin Mary and the communities that produced them over several centuries. He argues for the emergence of distinctly Chinese Catholic identities as artistic representations of the Virgin Mary sometime absorbed representations of such Chinese figures as Guanyin while at other times were diluted by Western influences following the influx of European missionaries. The book offers a new view of Cathol.
Illustrations; Acknowledgements; Introduction: Chinese Catholic identities in the modern period; Part 1: Images of Mary in China before 1842; 1. Chinese Christian art during the pre-modern period; Part 2: The Chinese Catholic Church since 1842; 2. After the treaties; 3. Our Lady of Donglu; 4. The rise and fall of the French protectorate; Part 3: Images of Mary in the early twentieth century; 5. The Furen art department; 6. The Chinese dimension to the Furen Christian art; Conclusion; Notes; Bibliography; Index; Plates
Description based upon print version of record.
Includes bibliographical references (pages [201]-263) and index.
Keywords: Chinese -- Philippines -- Manila -- Ethnic identity; Chinese -- Philippines -- Manila -- History; Chinese -- Philippines -- Manila -- Social conditions; Manila (Philippines) -- Commerce -- History; Merchants -- Philippines -- Manila -- History; Mary, -- Blessed Virgin, Saint -- Art; Catholic Church -- China -- History; Christian art and symbolism -- China -- History; Christianity and art -- Catholic Church; RELIGION / Christianity / Catholic; Electronic books; Electronic books